Utilização de extratos de plantas medicinais e óleo de Eucaliptus no controle in vitro de Microsporum canis - Frias, Danila Fernanda Rodrigues [UNESP]; Kozusny-Andreani, Dora Inês (My University, 2010)
INTRODUCTION: Microsporum canis is the most common cause of canine and feline dermatophytosis and thus has an important zoonotic role. OBJECTIVES: the aim of this study was to determine the antifungal action of medicinal plant extracts and of eucalyptus oil against pathogenic fungus Microsporum canis. METHODS: the extracts were prepared by mixing 300 g of previously washed leaves with 450 mL of distilled water. Then the material was triturated, filtered, sterilized and conserved at 10 + 2 oC. Fifteen milliliters of sterilized medium Sabouraud dextrose (Difco) at a temperature of 55 + 1 oC was added in Petri dishes containing the extracts in one, two, three, four and five mm concentrations. The fungus was inoculated once the medium was solidified. The inoculated dishes were maintained in B.O.D. incubator at 36 ± 0,5 oC until the fungus developed in the controls. RESULTS: the extracts from Punica granatum, Mangifera indica and Eucalyptus spp reduced the growth of fungus, but the extracts from Cymgopogom nardus, Tagetes minuta, Ruta graviolens, Cyperus rotundus, Annona moricata and Calendula spp leaves and flowers boosted the growth of fungus. The other extracts and the eucalyptus oil neither show any fungicidal action nor encourage mycelium growth. CONCLUSIONS: the use of most tested extracts and eucalyptus oil is not suitable for the treatment of Microsporum canis dermatophytosis due to lack of inhibitory effects. The extracts from Cymgopogom nardus, Tagetes minuta, Ruta graviolens, Cyperus rotundus, Annona moricata and from of Calendula spp leaves and flowers help the development of the fungus making clear that phytotherapy should be properly used, otherwise it can worsen the problem. However; extracts from Mangifera indica, Punica granatum and Eucalyptus spp. can be used as fungistatic.
Use of extracts of medicinal plants and oil of eucalyptus in the control in vitro of microsporum canis
Keywords: Dermatophyte; Fungistatic; Medicinal plants; Microsporum canis; Annona; Calendula; Cyperus; Cyperus rotundus; Eucalyptus; Felidae; Fungi; Lythraceae; Mangifera indica; Nardus; Punica granatum; Ruta; Rutaceae; Tagetes minuta